Sintesis Taganing Adaptif Menggunakan Metode Pitch Shifting by Delay-Line Based untuk Standardisasi Gondang Batak Toba - Pasto Juni Ansen Malau; Yohanes Suyanto (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2020)
This research using pitch shifting by delay line based method which consist of two main stage. The first stage is called analysis stage (framing, windowing, pre-emphasis and de-emphasis and FFT) that can detect the value of fundamental frequency of each taganing’s gendang. Then, this fundamental frequncy from each gendang will be classified into keyboard tones. The second one is called synthesis stage that will process the fundamental frequency become a new desire signal by creat an upward pitch change or a downward pitch change by delay line based method. Result of this research is created new signals as standard tones of each taganing’s gendang. The evaluation of synthesis output is using comparation method between fudamnetal frequency value of signal output as result of synthetis stage and the fundamental frequency value of keyboard standard’s tone. From the results of the system, it can be concluded  that taganing synthesis tone have  98.87% accuration rate.